THE RICH TAPESTRY OF TURKISH ANTHROPOLOGY: CULTURAL INSIGHTS AND SOCIETAL DYNAMICS - Hussain, Sajjad (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2024)
This study explores the field of anthropology in Turkey, emphasizing its historical development, key themes, and contemporary implications. Turkish anthropology arose during the late Ottoman Empire, influenced by Western methodologies and indigenous perspectives. The discipline has evolved to encompass various aspects of cultural identity, migration, and socio-political changes. Current anthropological work in Turkey examines how globalization and modernity are reshaping traditional lifestyles and cultural practices among Turkish communities. This paper aims to bridge established anthropological theories with new findings from Turkey, showcasing the richness of the country's cultural landscape through qualitative research methods. By synthesizing existing literature and presenting primary data, the research identifies key trends in Turkish anthropology and their relevance in a global context. Insights from this study contribute to broader discussions on cultural resilience, identity formation, and the role of anthropology in understanding complex social dynamics. The findings hold significant implications for future research directions and anthropological activism in Turkey.